2018
DOI: 10.1007/s00198-018-4635-1
|View full text |Cite
|
Sign up to set email alerts
|

Does primary lactase deficiency reduce bone mineral density in postmenopausal women? A systematic review and meta-analysis

Abstract: Postmenopausal women with PLD had lower Z-scores at most anatomic sites compared to healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Individuals homozygous for CC alleles in the lactase gene are not able to digest lactose, and tend therefore to consume less milk as compared with lactase persistent subjects, because of symptoms of lactose intolerance like flatulence, abdominal pain and diarrhea, resulting from the fermentation of undigested lactose in the large intestine. A meta-analysis comparing lactose absorbers to lactase-deficient subjects, as determined by genetic testing or breath hydrogen test, in five case–control studies, has not found a difference in areal BMD [ 66 ]. However, when expressed in Z score, i.e., age-adjusted, lumbar spine and total hip displayed lower BMD values in lactase-deficient subjects.…”
Section: Tolerance To Dairy Products and Safetymentioning
confidence: 99%
“…Individuals homozygous for CC alleles in the lactase gene are not able to digest lactose, and tend therefore to consume less milk as compared with lactase persistent subjects, because of symptoms of lactose intolerance like flatulence, abdominal pain and diarrhea, resulting from the fermentation of undigested lactose in the large intestine. A meta-analysis comparing lactose absorbers to lactase-deficient subjects, as determined by genetic testing or breath hydrogen test, in five case–control studies, has not found a difference in areal BMD [ 66 ]. However, when expressed in Z score, i.e., age-adjusted, lumbar spine and total hip displayed lower BMD values in lactase-deficient subjects.…”
Section: Tolerance To Dairy Products and Safetymentioning
confidence: 99%
“…A meta‐analysis of 18 randomized controlled trials revealed that lactose‐intolerant patients had significantly lower BMD in their hip joints compared to lactose‐tolerant individuals. This is likely due to reduced levels of plasma calcium, vitamin D, and PTH (Treister‐Goltzman et al., 2018).…”
Section: Dairy Products For the Prevention And Control Of Osteoporosismentioning
confidence: 99%
“…By this valuable article, we may further speculate that the ones with isolated lactase deficiency have the tendency to be diagnosed with osteoporosis, since the studies, the ones that were included into this meta-analyses, consisted of not only the lactose intolerant patients, but also the ones with isolated lactase deficiency [1].…”
mentioning
confidence: 98%
“…To the Editor, I have read Treister-Goltzman Y's article with a great interest since I have been working on the answer whether physicians have to treat the patients with isolated lactase enzyme deficiency [1]. By isolated lactase enzyme deficiency, I would rather refer to the patients with lactase deficiency determined by objective diagnostic tools, e.g., genetic analyses, direct enzyme activity measurement through intestinal biopsy or H 2 breath test, whereas presenting no lactose intolerance related symptoms [2,3].…”
mentioning
confidence: 99%